The effect of social network, funding and productive organizational energy on the capability of organizational ambidexterity in research institution - Novita Dyah; Rangga Almahendra (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2016)
The concept of organizational ambidexterity has been resonated and applied in diverse areas of management research. When establishing its strategic direction, research institutions are confronted with strategic tradesoffs, namely balancing the right amounts of exploration of new knowledge and exploitation of existing knowledge in their research orientation. We investigate this trade-off by building on the notion that research institution need to reconcile the paradoxical demands of exploitation and exploration in their orientation. The objective of this study is to examine the effect of social network, funding, and productive organizational energy on knowledge exploration, knowledge exploitation and the capability of organizational ambidexterity in the context of research institution. A sample of 130 research institutions such as laboratory, study center and training center was collected through questionnaire survey. We tested the hypotheses using Partial Least Square (PLS). Findings of the study indicate that social network and funding are positively related to knowledge exploration and exploitation. However, productive organizational energy has no positive effect on knowledge exploration and exploitation. It is also confirmed that knowledge exploration and knowledge exploitation have a significant influence on the capability of organizational ambidexterity, but knowledge exploitation has a dominant role on that effect.